Pengaruh Celebrity Endorsement Pada Media Sosial Instagram Terhadap Purchase Intention Pada ProdukPakaian Olahraga Adidas dengan Brand Image Sebagai Varibel Mediasi - Widiarsana, Nyoman Andika Bryan Prabawa (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
The development of the sports world has entered the realm of industry, where famous brands compete in marketing their products such as sportswear and sports equipment. It makes the famous brands compete in marketing their products, One of them by using social media Instagram and use celebrity endorsement.This research is aimed at determining and analyzing the direct and indirect celebrity endorsement on purchase intention on Adidas sportswear mediated by brand image as the intervening variable. This explanatory research explains the causal relationship between variables through hypothesis testingThrough non-probability sampling carried out on students in Malang who never bought any Adidas sportwear product, this research has selected 100 respondents as the sample. The hypothesis testing is done using t test and Sobel test. The data are analyzed using Partial Least Squares (PLS), supported by Smart PLS 3.0. Based on the four hypotheses, it can be concluded that the variable of celebrity endorsement has a positive and significant effect on the variable of brand image of Adidas Sportwear The variable of celebrity endorsement has a positive and significant effect on purchase intention Adidas sportswear. The variable of brand image has a positive and significant effect on customer’s intention to purchase Adidas sportswear. The variable of celebrity endorsement has a positive and significant impact on consumer’s intention to purchase Adidas sportwear mediated by brand imageKEYWORDS: Celebrity Endorsement, Brand Image, Purchase Intention